CIENCIA MARGINAL Colaboración de la Asociación jóvenes Amigos de la Ciencia - Guzmán López, Orlando; Miranda Caso Luengo, Alfonso; Cárdenas Guzmán, Guillermo; Salgado, Roberto (CIENCIA ergo-sum; Vol. 2 Núm. 1 (1995): CIENCIA ergo-sum (marzo-junio 1995), 2017)
-